2020
DOI: 10.3390/en13123262
|View full text |Cite
|
Sign up to set email alerts
|

Total Cost of Ownership Model and Significant Cost Parameters for the Design of Electric Bus Systems

Abstract: Without experiences of electric buses, public transport authorities and bus operators have faced questions about how to implement them in a cost-effective way. Simple cost modelling cannot show how costs for different types of electric buses differ between different routes and timetables. Tools (e.g., HASTUS, PtMS, and optibus) which can analyse such details are complicated, time consuming to use, and provide insufficient insights into the mechanisms that influence the cost. This paper therefore proposes a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Different types of transportation electrification entail distinct considerations. Electrifying bus stations requires evaluating service schedules and routes to determine the optimal placement of buses and chargers, along with devising a charging strategy aimed at minimizing overall costs, as demonstrated in [2][3][4][5][6][7][8][9][10]. Planning public electric charging stations for private EVs necessitates accounting for the unpredictable behaviors of vehicles.…”
Section: The Proposed Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of transportation electrification entail distinct considerations. Electrifying bus stations requires evaluating service schedules and routes to determine the optimal placement of buses and chargers, along with devising a charging strategy aimed at minimizing overall costs, as demonstrated in [2][3][4][5][6][7][8][9][10]. Planning public electric charging stations for private EVs necessitates accounting for the unpredictable behaviors of vehicles.…”
Section: The Proposed Modelmentioning
confidence: 99%
“…The TCO calculation demonstrated that opportunity charging has a slight cost advantage over depot charging. In [3], a method is proposed to calculate the total cost of ownership for different types of electric buses. In this model, the operating cost comprises the sum of the driver cost, energy cost, maintenance and insurance costs, and electric grid fees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other issues discussed in the literature are the environmental impact of the BEB operation (e.g., in [49][50]) and the economic assessment of the investment in BEBs (mainly in the form of a total cost of ownership calculation); see [51][52][53][54].…”
Section: Literature Studymentioning
confidence: 99%